Consolidación de la imagen corporativa de Adelca S.A. a través de las actividades sociales de responsabilidad social empresarial - Vallejo Barrera, María Salomé (2016)
Adelca SA is a company that started in 1963, with a group of Ecuadorian entrepreneurs that accepted the challenged to give the country a new and revolutionary Steel Industry, with a technical and economic way they sought to cover the needs of the construction and related products division. So they based on different forms of environmentally and friendly production systems (Adelca, 2015, p. web). Since its inception, Steelworks of Ecuador (Adelca S.A) has had immersed guidelines on Corporate Social Responsibility, in order to have a good relationship with its public, creating programs that benefit a hundred of customers and business partners. For this reason it decided to design a study directed to the image management from social activities of the organization, so their corporate social responsibility actions are an enhancer axis of the image to their audiences. First it will find a theoretical framework that contains authors and references about everything related to the solution of the problem with the company, and this will be solved from the guidelines and results arising from previous research, which will be held in the facilities of the organization. After we will develop a summary of the results found in the surveys and interviews with the people who belong to the community, customers and officials of Adelca S.A, this research has collected information provided by the company and data collected by the researcher of this study. To end a communicational proposal, this contains traditional and digital strategies that will manage the corporate image of the company in a simpler way, following guidelines and parameters determined by the needs of the organization and the concepts of the authors understood in these aspects.